An Unusual Presentation of Catatonia-Like Behavior: Differentiating Malingering from Catatonia - Wang, Andy Y.; Rehman, Urrooj H. (Case Reports in Psychiatry, 2021)
Malingering involves the intentional production of physical or psychological behaviors due to motivation from external incentives, posing unique challenges to healthcare. Although malingering as an entity has been well studied, the current literature does not explore the intentional production of catatonia-like behavior or how to differentiate malingering from catatonia. Here, we describe a 45-year-old female who was admitted to an acute psychiatric hospital with a complex presentation of catatonia-like signs that was ultimately thought to be volitional behavior, resulting in a diagnosis of malingering. We highlight the important factors considered in her presentation, the differences between her behaviors and true catatonia, and other important differential diagnoses to consider. Although a diagnosis of malingering is difficult to make, we underscore the importance of reaching this conclusion in order to avoid unnecessary and potentially harmful medical interventions. We stress the importance of shifting focus from medical management to more appropriate patient goals such as providing social services and treatment of other underlying psychiatric illnesses.